Comprehensive list of preventative migraine headache medications without significant drug–drug interactions - Dave, Jay; Hakkinen, Ian; Zhang, Pengfei (Frontiers in Neurology, 2024)
Background/objectivePreventive medications are crucial in migraine prevention. In cases of refractory migraine headaches, multiple medications may be required. We seek to identify a comprehensive list of preventive migraine headache medications that can be used as two, three, and four drug combinations without drug–drug interactions.MethodsWe compiled a list of prevention medications from Szperka et al.’s “Migraine Care in the Era of COVID-19” as well as American Headache Society’s 2018 and 2021 “Consensus Statements on Integrating New Migraine Treatments into Clinical Practice.” We obtained all possible two to four combinations of prevention medications through this list. We then filtered out all combinations containing at least one interaction based on DrugBank database and also identified least to most interacting medications.ResultsA total of 26 unique prevention medications are identified. This results in a total of 325 combinations of two preventives, 2,600 combinations of three preventives, and 14,950 combinations of four preventives. There are a total of 124, 146, and 0 non-interacting two, three, and four preventive combinations, respectively. All except 16 combinations of pick-twos can be placed within a pick-three combinations. The resulting distinct non-interacting medications can be represented by a condensed list of 162 unique combinations of medications. CGRP antagonists, Botulinum toxin A, melatonin, and candesartan are least interacting.ConclusionThis list of migraine preventive medications without drug–drug interactions is a useful tool for clinicians seeking to manage refractory headaches more effectively by implementing an evidence-based polypharmacy.